2018
DOI: 10.1177/0300060518792456
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dexmedetomidine and lidocaine on perioperative opioid consumption in laparoscopic intestine resection: a randomized controlled clinical trial

Abstract: NCT02616523.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 35 publications
0
38
0
1
Order By: Relevance
“…After reviewing the full text, 15 additional irrelevant trials were excluded. Finally, the articles considered to be suitable for this meta‐analysis consisted of 10 RCTs, enrolling a total of 527 adult patients. The search process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing the full text, 15 additional irrelevant trials were excluded. Finally, the articles considered to be suitable for this meta‐analysis consisted of 10 RCTs, enrolling a total of 527 adult patients. The search process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 studies, 2 studies were from Belgium; 2 studies were from Korea; 2 studies were from China; and the each of the remaining 4 studies were from France, Egypt, Lithuania, and Slovenia. All studies received IV lidocaine infusion before skin incision; five studies received IV lidocaine for more than 24 hours after surgery, and the other five studies infused lidocaine less than 24 hours after surgery. Most of the loading dose of lidocaine was 1.0 to 2.0 mg/kg, and continuous dose was 1.0 to 2.0 mg/kg/h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agonism of this alpha receptor induces multiple downstream effects including a decrease in sympathetic tone, attenuation of the neuroendocrine and hemodynamic response to surgery, reductions in anesthetic and opioid requirements, and induction of sedation and analgesia. There have been several studies assessing its benefit for postoperative analgesia when used during the perioperative period with mixed results [83][84][85][86][87][88][89][90][91][92][93][94][95][96]. However, many studies have demonstrated reduce postoperative opioid use when the drug is administered intraoperatively, specifically following laryngectomy [83], abdominal surgeries [84,95], bariatric surgery [91,96], cesarean section [86], off-pump coronary artery bypass surgery [87], knee surgery [88,94], tonsillectomy [90], and total abdominal hysterectomy [93].…”
Section: Dexmedetomidinementioning
confidence: 99%
“…However, many studies have demonstrated reduce postoperative opioid use when the drug is administered intraoperatively, specifically following laryngectomy [83], abdominal surgeries [84,95], bariatric surgery [91,96], cesarean section [86], off-pump coronary artery bypass surgery [87], knee surgery [88,94], tonsillectomy [90], and total abdominal hysterectomy [93]. A few studies have found a lack of benefit involving other types of procedures, including major spine [89] and some abdominal surgeries [85]. The dosing of dexmedetomidine for these studies differed significantly and ranged from a single pre-incision bolus to a continuous intraoperative infusion.…”
Section: Dexmedetomidinementioning
confidence: 99%